SISI NEGATIF GAME ONLINE PERSPEKTIF ISLAM DAN PSIKOLOGI ISLAM - Khotibul Umam; Abdul Muhid (State Islamic University (UIN) Ar-Raniry, 2020)
Technological development has changed human life style. Child's world that was once filled with traditional games has now been eroded by technological advances. Nowadays online games that replace traditional games are not only favored by children, almost all levels of human age like playing online games. But behind it all there is a negative impact that haunts its users. This study aims to reveal the negative side of using online games from the point of view of Islam and Islamic Psychology. The technique used is literature review by compiling some previous articles. The results showed that excessive use of online games will give a bad impact on the physical and psychological users, such as visual impairment, sleep disturbance, addiction, violence and stress. The use of online games is also considered more disadvantage than the benefits and it’s seen as an activity that wastes time, and it is prohibited in Islam.